Genomic and Metagenomic Insights Into the Microbial Community in the Regenerating Intestine of the Sea Cucumber Apostichopus japonicus - Zhang, Hongxia; Wang, Qing; Liu, Shilin; Huo, Da; Zhao, Jianmin; Zhang, Libin; Zhao, Ye; Sun, Lina; Yang, Hongsheng (Frontiers in Microbiology, 2019)
Host-intestine microbiota interactions have been widely studied in aquatic animals, but these interactions in the intestine regeneration process of the sea cucumber Apostichopus japonicus have been rarely investigated. To understand how intestine regeneration impacts the developing intestinal microbiome composition and function, we performed a case study to characterize the intestinal microbial composition and functional genes of A. japonicus during intestine regeneration stages. High-throughput 16S rRNA gene sequencing revealed significantly different intestine microbiota compositions in different regeneration stages. The phylogenetic diversity and composition of the intestinal microbiota changed significantly in the early regeneration stage and tended to recover in the end stage. During the regeneration process, the abundance of Bacteroidetes and Rhodobacterales increased significantly. A network analysis revealed that Rhodobacterales and Flavobacteriaceae may function as keystone taxa in the intestinal microbial community of A. japonicus during intestine regeneration. Metagenomic analyses of representative samples revealed that the microbiomes of regenerating intestines were enriched in genes facilitating cell proliferation, digestion and immunity. The increased abundance of Bacteroidetes elevated the enrichment of genes associated with carbohydrate utilization. Some functional features in the subsystem category changed in a pattern that was consistent with the changing pattern of microbiota composition during intestine regeneration. Our results revealed that seemingly regular alterations in the intestinal microbiome composition and function are associated with intestine regeneration stages. Intestinal microbiota can increase the abundance of beneficial bacterial members and upregulate related functional genes to adapt to intestine regeneration and reconstruct a stable community structure. This study provides a new insight into the mechanism of the host-microbiota interaction response to organ regeneration.